N-terminal diversity of Litopenaeus vannamei hemocyanin and immunity. (August 2019) - Fan, Jiaohong; Li, Xianmei; Lu, Hui; Lin, Ruihong; Aweya, Jude Juventus; Zhang, Yueling
Highlights: Different Litopenaeus vannamei tissues and individuals possess polymorphism in N-terminal of hemocyanin. The diversity of LvHMC-N could be modulated by pathogen challenge. Variants of LvHMC-N possess high agglutinative activities against Gram positive and Gram negative bacteria. Abstract: Hemocyanin is primarily a respiratory copper-containing glycoprotein present in the hemolymph of mollusks and arthropods. Recently, hemocyanin has attracted huge research interest due to its multifunctionality and polymorphism. Most previous immune-related studies on shrimp hemocyanin have focused on the C-terminal. Moreover, we previously reported that the C-terminal domain of Litopenaeus vannamei hemocyanin possesses single nucleotide polymorphisms (SNPs), but little is known about the molecular diversity of the N-terminal domain. In the current study, diversity within the N-terminal domain of L. vannamei hemocyanin (LvHMC-N) was explored using bioinformatics and molecular biology techniques as well as immune challenge. Twenty-five LvHMC-N variants were identified using polymerase chain reaction-denaturing gradient gel electrophoresis (PCR-DGGE) and DNA sequencing, with multiple sequence alignment showing that the 25 variants shared 87%–99 % sequence homology with LvHMC (AJ250830.1). In different shrimp individuals and different shrimp tissues ( i.e., hemocytes, stomach, muscle and hepatopancreas), the LvHMC-N variants were expressed differently. Pathogen challenge could modulate the molecular diversity of LvHMC-N, as three LvHMC-Nr variants (LvHMC-Nr1, LvHMC-Nr2 and LvHMC-Nr3) were identified by sequencing following Vibrio parahaemolyticus challenge. Most importantly, recombinant proteins of these three variants (rLvHMC-Nr1, rLvHMC-Nr2 and rLvHMC- Nr3) had relatively high in vitro agglutinative activities against V. parahaemolyticus, Vibrio alginolyticus and Streptoccocus iniae . Our present data indicates that the N-terminus of L. vannamei hemocyanin also possess molecular diversity, which seems to be associated with immune resistance to pathogenic infections.